Breaking Barriers; Building Resilience - Ahmed, Wajiha (Journal of Pakistan Psychiatric Society, 2026)
Mental-wellbeing is not the absence of adversity, it is the ability to go beyond what holds you back. Despite advancements in technology and pharmacology, the most important cure has always laid within us. Mankind’s gift of perseverance, our resilience. Often, we forget what we’re capable of, especially in the midst of calamity. Among others, one such vulnerable population is that of medical students. Increasing figures of depression, anxiety and burn out have been reported among medical students concurrent with seniority in clinical years. It is vital to ensure that we care for and empower the caregivers of tomorrow, therefore, equipping them with resilience today. Resilience begins as early as a child begins to walk, preparing one for stepping into bigger shoes as we grow.